The Perspective of Education of Teachers Having Vocation - Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 2001)
The article is dealing with the problem of perfection of teacher education. It draws attention to the phenomenon of “pedagogic vocation” giving a short description of its essence and structure and aims at showing it as an essential aspect in teacher education. Also a project of developing future primary school teachers' pedagogic vocation that has been worked out and put to the test at Klaipėda University is presented. The article stresses that understanding of teachers' subjective world and their professional self-concept may serve as a necessary precondition for the improvement the education of teachers at the university.
Keywords: Higher education; teacher education; professional self-concept; pedagogical vocation.